Antioxidant Activity, Total Phenolic Content and Chromatographic Fingerprints of the Herbal Extracts of Baihu Xiantan - Sutin, Soramon; Changtam, Chatchawan; Sopitthummakhun, Kittipat; Homvisasevongsa, Sureeporn; Meesin, Saowaluck; Sardsaengjun, Chanchai (KKU Science Journal, 2025)
The Baihu Xiandan formulation is a traditional Chinese herbal medicine renowned for its properties in tonifying Qi, strengthening the lungs and spleen, and nourishing Yin. This complex formula comprises 12 distinct medicinal herbs. Currently, the development and application of this specific formulation are exclusive to Hua Chiew Polyclinic, part of the Faculty of Traditional Chinese Medicine at Huachiew Chalermprakiet University. It is important to note that the formula lacks sufficient comprehensive research and study to date. This study aims to investigate the formula’s antioxidant activity, determine the total phenolic content, establish a chromatographic fingerprint, and quantify certain key compounds within the formula. To achieve this, each individual herb in the Bai Hu Xian Dan formula was extracted using three different solvents: ethyl acetate, ethanol, and water. Subsequently, the obtained extracts were subjected to antioxidant activity testing using both the DPPH and ABTS assays. The total phenolic content was also quantified. Furthermore, TLC fingerprinting was performed, and specific marker compounds were quantified using HPTLC technique. Results indicates that among the ethyl acetate, ethanol, and aqueous extracts, the following showed the best antioxidant activity using the DPPH method: Gancao, Lianqiao, and Jinyinhua. Their respective IC50 values were 49.60 ± 3.32 µg/ml, 39.39 ± 0.94 µg/ml, and 33.33 ± 2.10 µg/ml. For ABTS antioxidant activity, the ethyl acetate and ethanol extracts of Gancao demonstrated the strongest activity, with IC50 values of 11.87 ± 0.07 µg/ml and 30.68 ± 4.01 µg/ml, respectively. Among the aqueous extracts, Jinyinhua showed the best antioxidant activity, with an IC50 of 35.58 ± 0.41 µg/ml. Furthermore, the ethanol extract of the Bai Hu Xian Dan formula itself exhibited the best overall activity, with an IC50 of 87.98 ± 2.50 µg/ml. Regarding total phenolic content, the ethanol extract of Lianqiao had the highest amount, measuring 90.51 ± 1.59 mg GAE per gram of dry material. Ethyl acetate and ethanol extracts underwent TLC fingerprinting and quantification of chemical marker from the primary herbs in the formulation. Astragaloside II was found in the Huangqi extract at concentrations of 0.87% in the ethyl acetate fraction and 2.95% in the ethanol fraction. Additionally, 5-Hydroxymethylfurfural was found in the Dangsam extracts, with similar percentages in the ethyl acetate and ethanol extracts, at 1.58% and 1.65%, respectively. These data can be utilized as a basis for establishing quality control standards, supporting drug registration, and facilitating the further development of therapeutic agents.